Non-routine entrepreneurs: Another path of realizing entrepreneurial intentions - Alexander Chepurenko (Administrative Sciences, 2019)
The paper seeks to introduce the definition and to specify the characteristic features of "non-routine entrepreneurs". Using the notion of entrepreneurship by Shane and Venkataraman (2000), it explains "non-routine entrepreneurs" as persons driven primarily by the idea of exploring entrepreneurial opportunities, but less interested in being formally engaged in owing/managing a business or to claim additional incomes from it. The empirical base of the papers is two cases, labelled as a "patriot" and a "big tipster", from a panel of entrepreneurs, self-employees and start-ups the author surveyed in Moscow in three annual waves (2013-2015, N = 13). The paper shows the differences between the "non-routine entrepreneurs" and already well investigated groups (latent entrepreneurs, informal entrepreneurs, hybrid entrepreneurs, freelancers) and examines the personal (human capital) and social (transitional shock) context of the evolution of entrepreneurial intentions and their motivation. The "non-routine-entrepreneurs" fill in the lack of evidence about entrepreneurially minded persons with non-monetary goals, or non-economic meaning of results from such activities. Thus, the paper contributes to the literature on the reason and the intentionality of entrepreneurship. It concludes that "non-routine entrepreneurship" might become the choice of many people in contemporary societies where the boundaries between different kinds of economic activities are blurred.
Keywords: 350; non-routine entrepreneurs; entrepreneurial intentions; Russia; qualitative research